Interactional disparities in English and arabic native speakers with a bi-lingual robot receptionist - Fanaswala, I.; Browning, B.; Sakr, M. (2011 6th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2011)
HRI studies in a Middle Eastern environment are subject to nuances and subtleties. This study explores the nature of interactions, in an uncontrolled environment, between a permanently deployed bi-lingual robot-receptionist and interlocutors of varied native tongues. We correlate an interlocutor's native language with their propensity for accepting an invite and the duration of the ensuing conversation. Subsequently, we present results that demonstrate significant disparity in interactional patterns between English and Arabic speakers. We also assess the importance of a transliterated Arabic input mode for encouraging user interaction.